2018
DOI: 10.3389/fimmu.2018.00835
|View full text |Cite
|
Sign up to set email alerts
|

Targeting B Cells and Plasma Cells in Autoimmune Diseases

Abstract: Success with B cell depletion using rituximab has proven the concept that B lineage cells represent a valid target for the treatment of autoimmune diseases, and has promoted the development of other B cell targeting agents. Present data confirm that B cell depletion is beneficial in various autoimmune disorders and also show that it can worsen the disease course in some patients. These findings suggest that B lineage cells not only produce pathogenic autoantibodies, but also significantly contribute to the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
198
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(209 citation statements)
references
References 232 publications
(241 reference statements)
6
198
0
5
Order By: Relevance
“…Researches have shown that for antibody‐related autoimmune diseases, the combined treatment strategy targeting B cells and plasma cells is superior to B‐cell depletion therapy alone . Based on our clinical observations, we propose that it also can improve the prognosis of severe and refractory anti‐NMDAR encephalitis.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Researches have shown that for antibody‐related autoimmune diseases, the combined treatment strategy targeting B cells and plasma cells is superior to B‐cell depletion therapy alone . Based on our clinical observations, we propose that it also can improve the prognosis of severe and refractory anti‐NMDAR encephalitis.…”
Section: Discussionmentioning
confidence: 83%
“…Since anti‐NMDAR encephalitis is mainly mediated by humoral immunity, treatments targeting B cells and plasma cells are therapeutic . Rituximab is a monoclonal antibody directed against the CD20 surface antigen expressed on pre‐B cells, mature B cells, and memory B cells, but not plasma cells . Preliminary data suggested that the protracted clinical course of anti‐NMDAR encephalitis is due to antibody production by long‐lived plasma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting B cells and their differentiation into antibody-producing plasmablasts could constitute a promising treatment strategy for autoimmune diseases [8]. In this study, we intestigate the potential of novel chemical probes targeting epigenetic regualtors and thereby identify novel druggable tagets with the potential to modulate B-cell functionality also in B cells from autoimmune patients that may otherwise be more resistant to modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, several B-cell targeting therapies have been evaluated and some have moved forward to clinical development [8]. B-cell depletion by the anti-CD20 targeting monoclonal rituximab is approved for treatment of patients with rheumatoid arthritis and anti-neutrophil cytoplasmic antibody (ANCA)-vasculitis and is commonly used off-lable in several autoimmune conditions, but failed to meet the efficacy end-point in SLE.…”
Section: Introductionmentioning
confidence: 99%